A comparative study of gun sprinkler against non irrigation system in Ladang Risda Bukit Kota, Perak / Syafiah Salwa Mohd Rafidi - Mohd Rafidi, Syafiah Salwa (Faculty of Plantation and Agrotechnology, 2018)
In the plantation, irrigation is one of crucial management that need careful consideration and observation. As the gun sprinkler is still new and not widely used in oil palm plantation sector, the problem has inspired researcher to study on oil palm production response to gun sprinkler usage and economy feasibility of gun sprinkler to oil palm plantation in the term of production of yield, average bunch per weight and number of harvested bunches. This study is conducted at Ladang Risda Bukit Kota, Perak. Thus, the data obtained for this study is the data that was provided by the oil palm plantation. The result obtained from this study shown that in the term of productivity, there is no significant difference between gun sprinkler plot and non gun sprinkler plot. However, in the term of cost based on Benefit-Cost Ratio (BCR) analysis showed that gun sprinkler’s costs outweigh the benefits. It is due to several limitation that occurs during the study was conducted. In conclusion, gun sprinkler usage in oil palm plantation should not be considered. For the recommendation, the oil palm plantation company should used drip irrigation for their irrigation system as it shown by other researchers’ study that drip irrigation is more relevant than other irrigation system.